2017
DOI: 10.1093/annonc/mdw441
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II trial of cabazitaxel plus abiraterone in patients with metastatic castration-resistant prostate cancer (mCRPC) progressing after docetaxel and abiraterone

Abstract: BackgroundAbiraterone and cabazitaxel improve survival in patients with metastatic castration-resistant prostate cancer (mCRPC). We conducted an open-label phase I/II trial of cabazitaxel plus abiraterone to assess the antitumor activity and tolerability in patients with progressive mCRPC after docetaxel (phase I), and after docetaxel and abiraterone (phase II) (NCT01511536).Patients and methodsThe primary objectives were to determine the maximum tolerated dose (MTD) and dose-limiting toxicities (DLTs) of caba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…Androgen deprivation therapy (ADT) is the cornerstone of treatment for metastatic prostate cancer . Although most patients exhibit an initial response to ADT, most rapidly progress to castration‐resistant prostate cancer (CRPC) . With the deterioration of a patient's overall health and worsening symptoms, metastatic CRPC is invariably fatal .…”
Section: Introductionmentioning
confidence: 99%
“…Androgen deprivation therapy (ADT) is the cornerstone of treatment for metastatic prostate cancer . Although most patients exhibit an initial response to ADT, most rapidly progress to castration‐resistant prostate cancer (CRPC) . With the deterioration of a patient's overall health and worsening symptoms, metastatic CRPC is invariably fatal .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Massard and colleagues on the combination of cabazitaxel and abiraterone, also a lower incidence of grade !3 neutropenia was reported than in the TROPIC trial (56%). This lower incidence of neutropenia did not result in less (marker) efficacy, as PSA levels dropped in 46% patients (4).…”
Section: Discussionmentioning
confidence: 90%
“…Clinical studies with various combinations of therapies, for example, taxanes with novel hormonal therapies, with various designs and aims, are in progress (e.g., https:// clinicaltrials.gov/ct2/show/NCT02522715; refs. [2][3][4][5]. A summary of ongoing clinical trials on these combinations was recently reviewed by Sternberg, and showed the rationale for combination therapies (6).…”
Section: Introductionmentioning
confidence: 99%
“…Результаты КИ I/II фазы по применению комбинации кабазитаксела (25 мг/м 2 1 раз в 3 недели) с абиратероном (1000 мг/сут) после доцетаксела обнадеживают: частота ПСА-ответа достигла 46,2%, что выше, чем в регистрационных исследованиях кабазитаксела (39%) и абиратерона (29%). Профиль безопасности комбинации приемлемый [33]. Продолжается изучение кабазитаксела в комбинации с ИАС абиратероном и энзалутамидом.…”
Section: кабазитаксел в комбинации с другими агентамиunclassified